Pengaruh Online Customer Review dan Trust terhadap Keputusan Pembelian Produk Erigo pada Marketplace Lazada - Risnaldi Nur Aulia Hikmah; H. Ari Arisman; Suci Putri Lestari (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This research aims to find out: (1) Online Customer Reviews, Trust, and Purchasing Decisions at the Lazada Marketplace in the city of Tasikmalaya. (2) The relationship between Online Customer Reviews through Trust. (3) The influence of partial online customer reviews and trust on purchasing decisions for Erigo products at the Lazada Marketplace in Tasikmalaya city. (4) Simultaneous influence of Online Customer Review and Trust on purchasing decisions for Erigo products at the Lazada Marketplace in Tasikmalaya city. The research method used is a quantitative method with a survey approach. The data analysis technique used is Path Analysis with an interval measurement scale. Partial and simultaneous hypothesis testing with a significant level (α= 0.05). The research results show that: (1) Online Customer Reviews, Trust, and purchasing decisions for Erigo products on the Lazada Marketplace are included in the very good category. (2) Online Customer Review has a relationship with Trust in Erigo Marketplace Lazada products. (3) Online Customer Reviews and Trust have a positive and significant effect on Partial Purchase Decisions for Erigo products on the Lazada Marketplace. (4) Online Customer Reviews and Trust have a positive and significant effect on Simultaneous Purchasing Decisions for Erigo products on the Lazada Marketplace.